The school and university years of teacher Antonín Daniel - Závodská, Milada (Romano džaniben, 2018)
Antonín Daniel (1913–1996) – a greatly talented schoolchild, later a pupil of a secondary school, university student and finally a teacher by profession. The article describes his years at the elementary school, his student years at Ivančice secondary school and the final examination at the secondary school in Tišnov (1936). Subsequently, the article deals with the period until 1939, when he was a student of the Masaryk University in Brno, and the period 1945–1948, when he continued with his – by war circumstances forcedly interrupted – studies at two faculties: Faculty of Art and Faculty of Law at Masaryk University. During his institutional education, A. Daniel penned a number of texts in his native language, Moravian Romani, which were later published in the Journal of the Gypsy Lore Society. The article deals with the timeless value of Daniel’s early written work – i. e. Daniel’s history of his own birthplace Oslavany – but also with his active involvement in the translation of the biblical text The Acts of the Apostles into Romani. At the same time, the author of the article tries to consider various aspects of the institutional education of Roma in the interwar Czechoslovakia and their related connections in the social standing of the large families of Moravian Roma that A. Daniel came from.